SISTEM INFORMASI PENGURUSAN FORMULIR AKADEMIK UNTUK PENGAJUAN IJIN BELAJAR DAN TINGGAL BAGI MAHASISWA ASING DI INDONESIA (STUDI KASUS PADA INSTITUT SAINS DAN TEKNOLOGI AKPRIND YOGYAKARTA) - Hesty Dwi Suryaningsih; Erna Kumalasari; Rr Yuliana Rachmawati K (Jurnal SCRIPT, 2016)
The management information system architecture for academic forms for filing permits live and study for foreign students in Indonesia case study at Institute of science and Technology AKPRIND Yogyakarta is used to replace the old system which is still manual. So the purpose of this information system is expected to simplify and speed up in making the papers relating to the foreign students. The method that used for the research is a waterfall method with model analysis of OOADM (Object Oriented Analysis and Design Method) and the architecture of model design using UML (Unified Modeling Language). Design of manufacturing system using Yii Framework language, Postgre SQL and Apache Web Server. The results of this research are expected to form the academic management information system to permit the filing of a live and study for foreign students in Indonesia case study at Institute of science and Technology AKPRIND Yogyakarta can provide much convenience in the process of making the letters associated with foreign students so that more quickly and efficiently.